Cosmologia simplificada: uma sequência de ensino sobre cosmologia moderna no ensino médio - Winter, Ana Paula (2024)
In the current scenario full of possibilities for the insertion of different Digital Information and Communication Technologies (DICT) in Physics teaching, the motivation to explore online tools can prove to be an indispensable component for students' meaningful learning. Assuming that the more stimulated, curious and predisposed to learn, the student will become increasingly interested in the activities proposed for the study of Physics content. Based on this assumption, the Educational Product (EP) was created, under the title Simplified cosmology: a teaching sequence on modern cosmology in high school. The main objective of the experience with applying EP in teaching practice was to rescue some concepts and enrich the content seen in High School about Cosmology, to learn about instruments used by Observational Cosmology and to point out new observational perspectives that emerge in this direction. Observing Theory of Meaningful Learning, David Ausubel (2003), the academic content included in the EP was presented in the format of an online Educational Booklet and applied in investigative practice with didactic support from a Teaching-Learning Sequence (TLS), prepared with theoretical basis in Méheut and Psillos (2004). To analyze the results observed through the application of TLS/EP in pedagogical practice, the Content Analysis technique by Laurence Bardin (2011) was used. In the application of EP in the High School classroom, it was observed that the exploration of TLS with the support of the Educational Booklet as teaching material for consultation and the use of computerized mobile devices for access online brings together potential to innovate classroom dynamics in such a way as to make Physics classes more attractive, dynamic and productive.